2020
DOI: 10.3390/ani10040577
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cecal Commensal Microbiome Following the Insect Additive into Chicken Diet

Abstract: Gastrointestinal microbiota play an important role in regulating the metabolic processes of animals and humans. A properly balanced cecal microbiota modulates growth parameters and the risk of infections. The study examined the effect of the addition of 0.2% and 0.3% of Tenebrio molitor and Zophobas morio on cecal microbiome of broilers. The material was the cecum digesta. The obtained DNA was analyzed using 16S rRNA next generation sequencing. The results of the study show that the addition of a relatively sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 40 publications
3
37
0
1
Order By: Relevance
“…Moreover, the lack of any B. licheniformis influence is consistent with the results of Ren et al [57] and Ma et al [58], who used Lactobacillus agilis, L. salivarius, and B. subtilis DSM 3231. The main microbiota populations, i.e., Firmicutes, Proteobacteria, Actinobacteria, Tenericutes, and Bacteroidetes, were similar to those reported by Józefiak et al [59] and Pereira et al [47]. The favorable relation between Firmicutes and Bacteroidetes was noticed in the current study, which could be linked with the improvement of the birds' growth performance [60].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the lack of any B. licheniformis influence is consistent with the results of Ren et al [57] and Ma et al [58], who used Lactobacillus agilis, L. salivarius, and B. subtilis DSM 3231. The main microbiota populations, i.e., Firmicutes, Proteobacteria, Actinobacteria, Tenericutes, and Bacteroidetes, were similar to those reported by Józefiak et al [59] and Pereira et al [47]. The favorable relation between Firmicutes and Bacteroidetes was noticed in the current study, which could be linked with the improvement of the birds' growth performance [60].…”
Section: Discussionsupporting
confidence: 90%
“…As already reported by previous studies characterizing the cecal microbiota of light-size broilers fed diets containing TM meal [ 15 , 30 ], no differences were found in regards to α-diversity measures between the C- and the TM-fed birds of the present study. On the contrary, birds fed 15% level of HI meal inclusion recently displayed a lower Shannon index when compared to the C, 5% and 10% diets [ 16 ].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the decrease of Clostridium , Coprococcus , L- Ruminococcus and Ruminococcus above discussed suggests that TM meal utilization may negatively modulate the cecal microbiota of heavy-size broiler chickens. Previous studies characterizing the cecal microbiota of TM-fed light-size broilers revealed, however, overall positive insect-related effects in terms of increased abundance of potentially beneficial bacteria (such as Alistipes , Sutterella , and Clostridium [ 15 ], and Ruminococcus and Lactobacillus [ 30 ]). This contrasting outcome may be related to the different bird’s age (35 [ 30 ] and 40 [ 15 ] days vs. 53), as a partial confirmation of the wide influence of host-related factors on the poultry gut microbiota [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diptera metabolites [68] showed beneficial effects regarding the management of E. coli-induced diarrhea in mice by modulating the immune system, antioxidants and GM composition. The intestinal microbiota imbalance was reversed, as shown by the increase in Firmicutes to Bacteroidetes ratio and Clostridium levels caused by E. coli-induced diarrhea.…”
Section: Effect Of Chitin and Its Derivatives On Gut Microbiotamentioning
confidence: 99%